Biomarcadores de estresse oxidativo em carpas (Cyprinus carpio) expostas aos inseticidas carbofuran e fipronil em condições de lavoura de arroz - Clasen, Bárbara Estevão (2009)
The contamination of the aquatic environment by pesticides is a problem of global importance because of their toxic effect on non-target organisms. These products may affect toxicological parameters and oxidative stress in fish. The carp is cultivated in southern of Brazil and has great comercial interest. There are few studies in our country regarding the use of pesticides and their toxicity in these fish. The aim of this study was to determine if the insecticides used in rice farming alter these parameters in juvenile carp (Cyprinus carpio). Throught obtained results toxicity biomarkers to insecticides were determinated. The carps were exposed to insecticides for seven, 30 or 90 days in rice field condition. After the experimental periods, toxicological parameters and oxidative stress were evaluated in liver, brain and muscle. The parameters analyzed were the enzymatic activity of catalase (CAT) and glutathione S-transferase (GST). Furthermore, parameters of oxidative stress,such as protein carbonyl in the liver and levels of TBARS in the liver, brain and muscle were examined. The results showed that after exposure to the comercial formulation of the insecticide carbofuran the CAT increased its activity in hepatic tissue after 30 days of exposure. The enzyme activity was not changed in the liver of carp exposed to carbofuran for seven or 90 days. The GST decreased after seven and 90 days of exposure. On the other hand, after 30 days its activity increased in the liver of fish exposed to this insecticide. The protein carbonyl levels reduced in the liver of carp exposed for seven, 30 or 90 days to carbofuran. The TBARS levels increased in almost all tissues and periods considered, except the liver and brain that showed TBARS levels unchanged at seven days of exposure. Exposure to comercial formulation of insecticide fipronil showed that the activity of CAT reduced in all periods and tissues tested. The protein carbonyl levels increased after 30 days of exposure fipronil, while at seven and 90 days there was no change in the levels of protein carbonyl. The TBARS levels increased in all periods and tissues in carp exposed to fipronil. These results indicate that the measured parameters can be indicators of contamination to insecticides in Cyprinus carpio after prolonged exposure. According to the results obtained we consider the determination of protein carbonyl in hepatic tissue and TBARS in liver, brain and muscle tissue as biomarkers of carbofuran toxicity in carp after 90 days of exposure. For fipronil the results found in the activity of the CAT in liver and TBARS levels in all tissues studied, allow us to consider them biomarkers of insecticide toxicity.